Gry komputerowe i branża gier a sztuka komiksowa - Andrzej Klimczuk (COntextual MIX. Through Graphic Stories to Analyses of Contemporary Culture, Poznańskie Towarzystwo Przyjaciół Nauk, Poznań 2011, 2011)
Growth in popularity of computer (video) games is a noticeable change in recent years. Electronic entertainment increasingly engages the wider society and reaches to new audiences by offering them satisfy of wide variety of needs and aspirations. As a mass media games not only provide entertainment, but they are also an important source of income, knowledge and social problems. Article aims to bring closer look on the common areas of games and comics. On the one hand designers and artists working on games are often inspired by comic books, as well as they create their licensed adaptations and separate ,,interactive issues”. On the other hand more and more often we can see comics based on popular games. Study present the areas of agreement, cooperation or dependence like: technologies used to create games and comic books, use of comic books to comment events in the gaming industry and organization of exhibitions or events popularizing the works from both fields. – – W ostatnich latach dostrzegalny jest wzrost popularności gier komputerowych (wideo). Elektroniczna rozrywka angażuje uwagę coraz to szerszych kręgów społecznych i dociera do nowych grup odbiorców oferując im zaspokojenie najrozmaitszych potrzeb i aspiracji. Jako środek masowego przekazu gry dostarczają nie tylko rozrywki, ale stanowią też istotne źródło dochodów, wiedzy i problemów społecznych. Celem artykułu jest przybliżenie wspólnych obszarów gier i komiksu. Z jednej strony projektanci i artyści pracujący nad grami często czerpią inspirację z komiksów, jak również tworzą ich licencjonowane adaptacje i odrębne, ,,interaktywne numery”. Z drugiej zaś coraz częściej publikowane są komiksy bazujące na popularnych grach. Opracowanie przedstawia również takie obszary porozumienia, współpracy, bądź zależności jak: technologie wykorzystywane przy tworzeniu gier i komiksów, zastosowanie komiksów w komentowaniu wydarzeń branży gier oraz organizowanie wystaw i imprez popularyzujących twórczość z obu dziedzin.
Keywords: Z11; L82; 330; ICT; Ludology; Social Capital; Video Games; Mass media; Stereotypes and Prejudice; Game Concepts; Theory of Network & Participation Culture; serious games; e-learning; User-Generated Content; Technoculture; Comics Arts Education; Comics/Sequential Art; games industry; Leisure Industries